Osthole Ameliorates Estrogen Deficiency-Induced Cognitive Impairment in Female Mice - Adu-Nti, Frank; Gao, Xu; Wu, Jia-Min; Li, Jing; Iqbal, Javed; Ahmad, Riaz; Ma, Xin-Ming (Frontiers in Pharmacology, 2021)
Loss of endogenous estrogen and dysregulation of the estrogen receptor signaling pathways are associated with an increase in risk for cognitive deficit and depression in women after menopause. Estrogen therapy for menopause increases the risk of breast and ovarian cancers, and stroke. Therefore, it is critical to find an alternate treatment for menopausal women. Osthole (OST), a coumarin, has been reported to have neuroprotective effects. This study examined whether OST improves ovariectomy (OVX)-induced cognitive impairment, and alleviates anxiety- and depression-like behaviors induced by OVX in mice. Adult female C57BL/6J mice were ovariectomized and then treated with OST at a dose of 30 mg/kg for fourteen days. At the end of the treatment period, behavioral tests were used to evaluate spatial learning and memory, recognition memory, anxiety- and depression-like behaviors. A cohort of the mice were sacrificed after 14 days of OST treatment and their hippocampi were collected for the measurement of the proteins of interest using western blot. OVX-induced alteration in the levels of proteins was accompanied by cognitive deficit, anxiety- and depression-like behaviors. OST treatment improved cognitive deficit, alleviated anxiety- and depression-like behaviors induced by OVX, and reversed OVX-induced alterations in the levels of synaptic proteins and ERα, BDNF, TrKB, p-CREB, p-Akt and Rac1 in hippocampus. Therefore, reversal of OVX-induced decrease in the levels of above proteins in hippocampus by OST might contribute to the effects of OST on improving cognitive deficit and alleviating anxiety- and depression-like behaviors induced by OVX.